A Preliminary Motivational Evaluation of Milestone-Based Laboratory Assessment - Stanton, K.; Lindsey, Euan (Stipes Publishing LLC, 2011)
Milestone based marking is an asynchronous assessment approach used for semester-long projects. By providing students with a fine-grained marking scheme – the milestones – at the start of semester, and allowing students to claim these marks at any point in the semester, students can better plan and self-manage their learning. The milestone-based assessment approach is intended to motivate the students by making the assessment process transparent and accessible. To determine whether or not this has occurred, it is necessary to evaluate the initiative through the lens of motivation theories. Since the connection between motivation and learning is well understood, looking specifically at motivation should shed light on how deeply students are learning in this new approach. In this paper, student data from three semesters of implementation is reviewed and explained using various motivation theories: Self-Determination Theory, Flow Theory, Self-Efficacy Theory, Goal Theory, and Expectancy-Value Theory. Results show that many of these theories have opportunity to explain the students’ engagement and learning and provide insight into how better to examine student motivation in upcoming semesters.